2022
DOI: 10.21203/rs.3.rs-1680830/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification and Validation of a Novel Prognostic Model Based on Platinum Resistance-Related Genes in Bladder Cancer

Abstract: Background: Bladder cancer (BC) is a heterogeneous disease with high recurrence rate. The depth of response to platinum-based chemotherapeutic agents in urothelial neoplasm tissues varies greatly. Biomarkers that have practical value in prognosis stratification and early determination of therapeutic effect are increasingly needed. Our study aimed to select a set of BC-related genes involved in both platinum resistance and survival, then use these genes to establish the prognostic model.Methods: Platinum resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Dr. Hao and collegues from China performed in page 61 ( 5 ) a study about the identification and validation of a novel prognostic model based on platinum Resistance-related genes in bladder and concluded that a prognostic model derived from platinum resistance-related genes was constructed, we confirmed its value in predicting platinum-based chemotherapy benefits and overall survival for BC patients. The model might assist in therapeutic decisions for bladder malignancy.…”
mentioning
confidence: 74%
“…Dr. Hao and collegues from China performed in page 61 ( 5 ) a study about the identification and validation of a novel prognostic model based on platinum Resistance-related genes in bladder and concluded that a prognostic model derived from platinum resistance-related genes was constructed, we confirmed its value in predicting platinum-based chemotherapy benefits and overall survival for BC patients. The model might assist in therapeutic decisions for bladder malignancy.…”
mentioning
confidence: 74%